The effect of diets incorporating Mucuna (Mucuna pruriens) seed meal on the performance of laying hens and broilers - E.A. Iyayi (Tropical and Subtropical Agroecosystems, 2003)
The effect of incorporating Mucuna (Mucuna pruriens) seed meal on the performance of laying hens and broilers was investigated. In the first experiment, one hundred 18-week old black Nera birds were randomly allocated on body weight basis to 4 experimental diets. In diets 1, 2, and 3, 40% soybean meal was replaced with autoclaved (AMSM), raw (MSM) and roasted (RMSM) Mucuna seed meal, respectively. As soybean meal contained 15% of the diets in the control diet (Diet 4), the level of Mucuna seed meal in the diets was 6%. Each dietary treatment had 25 birds distributed to 5 replicates of 5 birds. The feed consumption of laying hens fed the raw Mucuna seed diet was reduced (P<0.05) while the feed consumption of birds on the control, AMSM and RMSM Mucuna seed treatments was similar. None of the Mucuna diets had effect on egg size as the egg weights, lengths and widths were similar across all the treatments. Egg yolk index did not significantly change by feeding any form of Mucuna diet. There were no meat or blood spots in the eggs. In the second experiment, 160 day-old broiler chicks were randomly allocated to four dietary treatments in a completely randomized design. The diets were formulated in a way that roasted Mucuna seed meal (RMSM) replaced soybean meal in a conventional broiler diet by 0, 33.3, 66.7 and 100% at both the starter and finisher phases. The final levels of RMSM in the diets were therefore 0, 6, 12 and 18% at the starter phase and 0, 5, 10 and 15% at the finisher phase. For broilers, 12 and 18% RMSM reduced (P<0.05) body weight gain and feed consumption at the starter and finisher phases. None of the levels of RMSM affected efficiency of feed utilization, or weights of gizzards and hearts. Addition of 6% RMSM had no effect on the organ weights but weights of air sacs, small and large intestine and caeca were reduced while those of liver and spleen were increased at 12 and 18% RMSM. The 18% RMSM resulted in various degenerative syndromes in the organs of the birds. Results of the studies suggest (i) that 6% processed Mucuna seed meal in the diets of layers had no adverse effect on egg qualities and (ii) broilers raised on diets containing 6% RMSM performed as well as those fed on sole soybean meal diet. Levels higher than 6% caused a reduced performance of the birds because the antinutritional factors in Mucuna disrupted the digestive tract and organs.